Newman’s Poetry: The Heart of a Victorian Renaissance Project - Dampi Somoko (Cahiers Victoriens et Edouardiens)
This paper examines the poetry of John Henry Newman (1801–1890) in the context of the revival movement in the Victorian era. Although poetry does not make up the bulk of his writings, it can still be a vehicle for a return to distant literary sources in the interests of revival. This is particularly true of the poetic dream in The Dream of Gerontius, which borrows characteristics from both the anonymous Old English poem The Dream of the Rood and Dante’s Divine Comedy. This creative recourse to old literary and aesthetic sources as an inspiration is marked by porosity, hybridity, and subversion when the mutation of the character takes place in a gradual process from de-personification to kenosis. The poetic journey as well as the passage from life to death are addressed in renewed forms, figures and motifs.